Gene Signature of Proliferating Human Pancreatic α Cells - Dominguez Gutierrez, Giselle; Xin, Yurong; Okamoto, Haruka; Kim, Jinrang; Lee, Ann-Hwee; Ni, Min; Adler, Christina; Yancopoulos, George D; Murphy, Andrew J; Gromada, Jesper (Endocrinology (Philadelphia), 2018)
Pancreatic α cells proliferate at a low rate, and little is known about the control of this process. Here we report the characterization of human α cells by large-scale, single-cell RNA sequencing coupled with pseudotime ordering. We identified two large subpopulations and a smaller cluster of proliferating α cells with increased expression of genes involved in cell-cycle regulation. The proliferating α cells were differentiated, had normal levels of GCG expression, and showed no signs of cellular stress. Proliferating α cells were detected in both the G1S and G2M phases of the cell cycle. Human α cells proliferate at a fivefold higher rate than human β cells and express lower levels of the cell-cycle inhibitors CDKN1A and CDKN1C. Collectively, this study provides the gene signatures of human α cells and the genes involved in their cell division. The lower expression of two cell-cycle inhibitors in human α cells could account for their higher rate of proliferation compared with their insulin-producing counterparts.